Epidural Abscess Caused by Gas-Producing Clostridium Septicum: A Case Report. Issue 4 (October 2019) - Money, Adam J.; Molloy, Seth; Grabowski, Gregory
Abstract : Case: Few cases have reported Clostridium species of bacteria as a source for vertebral osteomyelitis and epidural abscesses. The subspecies of Clostridium septicum has not been described as a cause. This case describes a 69-year-old man who hematogenously spread C. septicum without associated malignancy, subsequently failed conservative management in the form of intravenous antibiotics, and was definitively treated with surgical intervention through a minimally invasive approach. Conclusions: An epidural abscess occurring in a surgically naive patient is a rare phenomenon. An epidural abscess caused by C. septicum is even rarer. Appropriate imaging, early recognition, and surgical debridement can lead to a favorable outcome.